Spirituality in nursing: An analysis of the concept - S.N. Mahlungulu; L.R. Uys (AOSIS, 2004)
There is scientific evidence that the spiritual well being of a person can affect quality of life and the response to illness, pain, suffering and even death. In spite of this evidence, spirituality in nursing has not been examined within a South African context. The purpose of this study was to describe the phenomenon of spirituality from the perspective of nurses and patients/clients with the aim of generating a middle range theory of spiritual care in nursing. A qualitative mode of inquiry using a grounded theory method was applied. A sample of 56 participants composed of 40 nurses, 14 patients and 2 relatives of patients was recruited by theoretical sampling procedure from one public hospital, one private hospital and one hospice setting. Focus group interviews and one on one in depth interviews were conducted. An audio tape recorder was used to record the interviews. Field notes and memos were also kept.